Behavioural disorders amongst children of a rural community of Lucknow, India - Rajpurohit, AC; Haque, Mohd. Afzalul; Nigam, Vijay Shanker; Ahuja, Ravindra; Srivastava, Vinay P; Srivastava, Vinod K (Indian Journal of Community Health, 2016)
Background: Behavioural disturbances are notable child health problem, the importance of which is increasingly recognized in most countries. A behaviour problem is nothing but a deviation from the accepted pattern of behavior on the part of the child when he is exposed to an inconsistent social and cultural environment. Aims & Objectives: To assess the prevalence of behavioural disorders in children of a rural community. Material & Methods: This was a village based cross-sectional study done among the children for the assessing the behavioural disorders. Results: Of the total 1157 children studied, 195 (16.9%) showed one or the other behavioural disorders. Various disorders elicited were bed wetting (11.6%), thumb sucking (3.1%), nail biting (1.6%) and food fad (0.5%). The disorders were more common in preschool children (34.2%) compared to school going age children (11.0%). Behavioural disorders were more frequent in children at extremes of birth orders (birth orders I & V) compared to others. The prevalence of disorders did not differ much in boys (16.2%) and girls (17.6%). Conclusions: The present study has reported a relatively higher prevalence of behavior disorders (16.9%) in children in a rural setting. The pattern of behavior problems was studied in terms of age, sex and birth order. In such children, there is a need for health education and counseling by psychiatrist/psychiatric social worker at the primary care level and must be worked out